The Factors That Affect Customer Value and Its Impact on the Customer Loyalty - Jefry Rom Donny; Undang Juju; eddy Jusuf; Maskarto Lucky Nara Rosmadi (Budapest International Research and Critics University, 2018)
This study aims to find out and analyze the factors that influence customer value and their impact on customer loyalty. This study uses quantitative methods with descriptive and verification approaches using explanatory surveys. The analysis technique uses SEM analysis. From the results of the study obtained data that the factor of consumer psychology moves from the point of not good to good while the customer value factors and customer loyalty moves from good enough to well. Verification results show both partially and simultaneously these factors have a positive and significant effect. Customer value has a positive and significant effect on customer loyalty with the magnitude of its influence stronger when compared to consumer psychology and the marketing mix towards customer value. This proves empirically that customer value factors are intervening between consumer psychology and marketing mix with customer loyalty.